PENGARUH MOTIVASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI PERSON ORGANIZATION FIT (STUDI PADA PEGAWAI NEGERI SIPIL SEKRETARIAT DAERAH KABUPATEN DEMAK) - Wulandari, Lina; Tjahjaningsih, Endang (Jurnal Ilmiah Telaah Manajemen, 2017)
This study has aimed to examine and to analyze the influence of motivation and quality work of life on employee performance with person organization fit mediation on Civil Servant Employees Sekretariat Daerah Kabupaten Demak. Data collection used survey method for 110 respodens. They were Civil Servant Employees on Sekretariat Daerah Kabupaten Demak with slovin methode. The technique of data testing used statistical method, they covered validity test, reliability test, regression analysis, t-test and mediation test. They were used to test and to prove hypotheses of study. Based on resulting of their analysis, its examining pointed out motivation did not influence for person organizatio fit while quality work of life influence positive and significant for person organization fit. Motivation and quality work of life influence positive and significant for employee performance. Keywords: motivation, quality work of life, person organization fit and employee performance.